Bacterial Sexually Transmitted Disease Screening Outside the Clinic—Implications for the Modern Sexually Transmitted Disease Program - Bernstein, Kyle T. (Sex Transm Dis, 2016)
BACKGROUND: The development of noninvasive nucleic acid amplification tests for chlamydia and gonorrhea has facilitated innovation in moving sexually transmitted disease (STD) screening to nonclinical settings. However, limited data are available to inform local STD programs on evidence-based approaches to STD screening in nonclinical settings in the United States. METHODS: We conducted a systematic review of the literature published since 2000 related to chlamydia, gonorrhea, and syphilis screening in US correctional settings, bathhouses and sex venues, self-collected at-home testing, and other nonclinical sites. RESULTS: Sixty-four articles met eligibility criteria and were reviewed. Although data on testing volume and positivity were available, there were scarce data on the proportion of new positives treated and the programmatic costs for the various screening programs. Screening in correctional settings identified a sizable amount of asymptomatic infections. The value and sustainability of screening in the other nonclinical settings examined was not clear from the published literature. CONCLUSIONS: Local and state health departments should explore the development of sustainable jail and juvenile detention screening programs for STDs. Furthermore, local programs should pilot outreach and home-based STD screening programs to determine if they are identifying asymptomatic persons who would not have otherwise been found. Local programs are encouraged to present and publish their findings related to non–clinic-based screening to enhance the limited body of literature; data on the proportion of new infections treated and the local program costs are needed.